CAREER GUIDANCE WORK BASED ON THE FORECAST NEEDS OF THE LABOR MARKET OF THE KURSK REGION, AS A TOOL FOR RETAINING STAFF - Nadein V. V., Diomich I. E. (Economics and Management: Theory, Methodology, Practice, 2020)
The personnel potential of the population is a significant factor affecting the successful development of the economy of the region and the country as a whole. The outflow of personnel, the imbalance in the human system, the low level of employment of graduates of vocational education, youth unemployment – all this is a serious problem, particularly due to lack of demand and the low prestige of the profession in a given place and time. This problem requires close attention from the educational authorities to the issues of career guidance, including in terms of its orientation on the basis of the economic state of the labor market.
Keywords: человеческий капитал; human capital; образование; career guidance; безработица; education; рынок труда; labor market; профориентационная работа; outflow of personnel; unemployment; Kursk region; labor stimulation; отток кадров; Курская область; стимулирование труда